2016
DOI: 10.1111/jcmm.12826
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐associated macrophages correlate with microvascular bed extension in colorectal cancer patients

Abstract: Tumour‐associated macrophages (TAMs) represent pivotal components of tumour microenvironment promoting angiogenesis, tumour progression and invasion. In colorectal cancer (CRC), there are no conclusive data about the role of TAMs in angiogenesis‐mediated tumour progression. In this study, we aimed to evaluate a correlation between TAMs, TAM immunostained area (TAMIA) microvascular density (MVD), endothelial area (EA) and cancer cells positive to VEGF‐A (CCP‐VEGF‐A) in primary tumour tissue of locally advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…In this study, it was found that there was a significant correlation between macrophage infiltration and microvascular density in a series of tumors from 76 CRC patients. Therefore, TAMs could be used as a marker for angiogenesis-mediated CRC [50]. …”
Section: The Role Of Tams On Tumor Angiogenesis Crc Growthmentioning
confidence: 99%
“…In this study, it was found that there was a significant correlation between macrophage infiltration and microvascular density in a series of tumors from 76 CRC patients. Therefore, TAMs could be used as a marker for angiogenesis-mediated CRC [50]. …”
Section: The Role Of Tams On Tumor Angiogenesis Crc Growthmentioning
confidence: 99%
“…To this regard, it is important to underline that MCs can stimulate neovascularization releasing mainly tryptase stored in their secretory granules [38,39]. …”
Section: Discussionmentioning
confidence: 99%
“…Conflicting data exist whether macrophages and which subtype contribute to CRC progression. [13][14][15][16][17] Lymphocytes also provide defense functions in order to maintain the integrity of the epithelial barrier within the healthy intestinal mucosa. 18 These cells have an activated yet resting manifestation 19 and the memory phenotype is enriched among T cells.…”
Section: Introductionmentioning
confidence: 99%